2022
DOI: 10.1155/2022/3077691
|View full text |Cite|
|
Sign up to set email alerts
|

The Application of a Multidimensional Prediction Model in the Recurrence of Female Pelvic Organ Prolapse after Surgery

Abstract: Objective. The relationship between multiple indicators of women and postoperative recurrence of pelvic organ prolapse was analyzed to establish a model for predicting postoperative recurrence of female pelvic organ prolapse. Methods. Three hundred patients with pelvic organ prolapse who underwent pelvic organ prolapse surgery at our hospital were monitored for 1-2 years to determine their prognosis. Whether there was a postoperative recurrence, they were divided into two groups. We collected the relevant data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…By keywords citation bursts analysis, the time-series showed that validation, lifetime risk, native tissue Frontiers in Bioengineering and Biotechnology frontiersin.org repair, tissue engineering and mesenchymal stem cells had appeared most recently. This result shows that clinical research is still the hot research topic of POP research, and prediction models and tissue engineering are research priority (Laursen et al, 2022;Oh et al, 2022;Zhang et al, 2022). In essence, overcoming mesh complications through increasing technical strategies is the core problem of pelvic floor reconstruction surgery.…”
Section: Rankmentioning
confidence: 99%
“…By keywords citation bursts analysis, the time-series showed that validation, lifetime risk, native tissue Frontiers in Bioengineering and Biotechnology frontiersin.org repair, tissue engineering and mesenchymal stem cells had appeared most recently. This result shows that clinical research is still the hot research topic of POP research, and prediction models and tissue engineering are research priority (Laursen et al, 2022;Oh et al, 2022;Zhang et al, 2022). In essence, overcoming mesh complications through increasing technical strategies is the core problem of pelvic floor reconstruction surgery.…”
Section: Rankmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%